PARTISIPASI ANGGARAN, REINFORCEMENT CONTINGENCY, DAN BUDGETARY SLACK - Fara Fitriyani (Tirtayasa Ekonomika, 2017)
The purpose of this research was to determinethe effect of budget participation on budgetary slack using reinforcement contingency as a moderating variable. The population in this research are subordinatesonUniversity in Banten. Sampling method using purposive sampling with the number of samples that meet the criteria as much as 79 respondents.The questionnaire was tested with a test of reliability and validity, further testing of the classical assumptions include normality test, multicollinearity test, and heteroscedasticity test. Then the hypothesis testing is done by regression analysis The results are all variables reliable and valid and full fill classic assumption. The result of hypotheses analysis show that budget participation have positive and significance effect on budgetary slack. Furthermore, reinforcement contingency doesn’t moderate the relationship of budget participation and budgetary slack.